2016
DOI: 10.1186/s12885-016-2984-8
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and predictive significance of long interspersed nucleotide element-1 methylation in advanced-stage colorectal cancer

Abstract: BackgroundHypomethylation of Long Interspersed Nucleotide Element-1 (LINE-1) is associated with worse prognosis in colorectal cancer (CRC). However, little is known about the relevance of this marker for the prognosis and response to chemotherapy of metastatic and recurrent (advanced-stage) CRC. Our aim was therefore to investigate whether tumor LINE-1 hypomethylation correlates with patient survival and with response to 5-fluorouracil (5-FU)/ oxaliplatin (FOLFOX) chemotherapy in advanced-stage CRC.MethodsThe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…Subsequent studies have confirmed the relationship between LINE-1 hypomethylation and poor prognosis in resected colorectal cancers [15-18]. In addition, LINE-1 hypomethylation has been reported to correlate with unfavorable outcomes in colon cancer patients receiving oxaliplatin with fluorouracil and folinic acid adjuvant chemotherapy [19-21]. …”
Section: Line-1 Methylation Level and Prognosis In Gi Cancersmentioning
confidence: 72%
“…Subsequent studies have confirmed the relationship between LINE-1 hypomethylation and poor prognosis in resected colorectal cancers [15-18]. In addition, LINE-1 hypomethylation has been reported to correlate with unfavorable outcomes in colon cancer patients receiving oxaliplatin with fluorouracil and folinic acid adjuvant chemotherapy [19-21]. …”
Section: Line-1 Methylation Level and Prognosis In Gi Cancersmentioning
confidence: 72%
“…If peripheral blood miRNA is used as a tumor marker in clinic, reference range should be established and a standardized system should be established to ensure the accuracy and repeatability of miRNA detection. An increasing level of methylated DNA was association with advanced stage of colorectal cancer [50,51]. But the speci city of methylation detection is low.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, Barciszewska et al (2007) found lower 5mC level is correlated with advanced malignancy grade in breast and colon cancer. Improved patients‘ survival with global hypermethylation levels baseline ( Kaneko et al, 2016 ). In addition, LINE-1 hypermethylation is negatively associated with the T- stage and lymph node metastases in CRC patients ( Morikawa et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%